Bees rising from the ashes? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Writing from Wolaita Soddo in Ethiopia, Alemseged Mengesha asks 'Is there something secret? One morning I was called away from my breakfast and I left half a cup of tea on the table. When I came back after an hour, the glass was full of dead...